Phosphodiesterase-4 Inhibitors for the Treatment of Inflammatory Diseases - Li, Heng; Zuo, Jianping; Tang, Wei (Frontiers in Pharmacology, 2018)
Phosphodiesterase-4 (PDE4), mainly distributing in immune cells, epithelial cells and brain cells, manifests as an intracellular non-receptor enzyme modulating inflammation and epithelial integrity. Inhibition of PDE4 is predicted to have broad biological effects via elevating the level of cyclic adenosine monophosphate (cAMP) and related pathways and subsequently regulating a wide array of genes and proteins. PDE4 has been identified to be a therapeutic target for treating diverse pulmonary, dermatological and severe neurological diseases. Over the past decades, numerous PDE4 inhibitors have been designed and synthesized, among which roflumilast, apremilast and crisaborole were approved in treating inflammatory airway diseases, psoriasis arthritis and AD, respectively. It’s regrettable that the dramatic efficacies are often accompanied by nausea, emesis or gastrointestinal reactions in the further clinical application. Better yet, substantial advances have been obtained to mitigate the adverse effects and obtain better benefit-to-risk ratio. This review highlights the dialectical role of PDE4 in drug discovery and disquisitive details of certain PDE4 inhibitors to provide an overview of topics that still need to be addressed in the future.